Community Empowerment Through CSR Practices: The Si Pandu & Desi Program by PT PLN Nusantara Power UP Tanjung Awar-Awar - Gratha Ayunisa Agsyanti; Yunan Kurniawan; Sucinata Agung Priambada; Bilal Joko Suratno (Prospect Publishing, 2025)
Si Pandu & Desi is a CSR initiative by PT PLN Nusantara Power UP Tanjung Awar-Awar that focuses on implementing various innovations in the agricultural sector. The program originates from regional challenges faced by communities in Wadung, Kaliuntu, and Beji Villages, particularly in managing agriculture sub-optimally. Issues such as low productivity and the environmental risks arising from poor agricultural waste management have become the main focus of the program’s development. The initiative includes the provision of physical capital through the SATRIA PADU facility, as well as the enhancement of human capital through community empowerment. Program implementation is centered around the application of the Creating Shared Value (CSV) concept to support sustainability for the company, farmers, and livestock producers.